JORDAN DERIVATIONS on ïï M-MODULES - Salih, salah Mehdi (MAGISTRA, 2014)
The aim object of this paper is present the definitions of drivation, Jordan derivation and Jordan triple derivation on âM-module also we prove that every Jordan derivation of â-ring M into 2-torsion prime ïï-module X is a derivation of M into X. Mathematics Subject Classification: 16W30, 16W25. Keywords: semiprime ïï-module, derivation.